Performance Characteristics of Anaerobic Biodegradation of Synthetic Phenolic Industrial Wastewater - Singh, Mishu (JPAIR Multidisciplinary Research, 2015)
The treatment of toxic and inhibitory phenolic compounds using biological techniques have been pursued vas a promising and widely accepted treatment process due to its easiness of handling, a greater level of stabilization of waste and properly operated to prevent the production of secondary pollutants. Up-flow Anaerobic Bio-Reactors (UAFB) has been widely applied for the handling of high organic load industrial wastewater. The treatment of synthetic phenolic wastewater by a single stage anaerobic fixed bed bioreactor with granite stones packing at four different temperatures was studied. The effect of hydraulic retention time on COD reduction and other steady state characteristics and kinetic parameters, which form these characteristics, was also studied. A recirculated single stage up-flow anaerobic bioreactor operated at all the above-given temperatures with initial BOD 1462 mg/l and initial COD 5720 mg/l for a digestion period of 25 days with a working volume of 1000 ml. The performance of the reactor was monitored after every five days and analyzed in terms of percentage (COD, BOD, TS, TDS, VS removal and biogas production). The removal efficiency of BOD, COD, TS, TDS and VS reached a maximum value of 63.20%, 61.24%, 44.88%, 47.67% and 53.12% respectively. With the change in HRT, the maximum COD reduction was 66.04% at 24 hrs HRT at 400C with initial COD of 5000 mg/l. Specific biogas yield increased up to 0.0162 ml/mg CODr.
Keywords: Phenol; anaerobic; fixed bed bioreactor; wastewater; up-flow anaerobic sludge blanket; experimental design; India